German experience of financing of economic development of regions Опыт Германии в финансировании экономического развития регионов - Derkach Nikolay I. (Bìznes Inform, 2012)
The strategy of regional development of Germany, system of the interbudgetary smoothing of Germany are analysed in the article. The features of forming of profitable part of local budgets in Germany are investigational. Practical recommendations in relation to introduction of German experience of financing of regional development in Ukraine are developed. В статье проанализована стратегия регионального развития Германии, система межбюджетного выравнивания Германии, исследованы особенности формирования доходной части местных бюджетов в Германии, разработаны практические рекомендации относительно внедрения немецкого опыта финансирования регионального развития в Украине.